NF-kB-regulated exosomal miR-155 promotes the inflammation associated with arsenite carcinogenesis. (1st March 2017) - Chen, Chao; Luo, Fei; Liu, Xinlu; Lu, Lu; Xu, Hui; Yang, Qianlei; Xue, Junchao; Shi, Le; Li, Jun; Zhang, Aihua; Liu, Qizhan
Abstract: In the cancer microenvironment, extracellular communication allows various types of cells to coordinate and execute biological functions. Emerging evidence indicates that exosomes, as mediators of cell communication, are involved in tumor progression. Little is known, however, about the mechanism by which exosomal miRNAs regulate inflammatory infiltration in arsenite-induced liver cancer. The present research aimed to determine if miRNAs secreted from arsenite-transformed human hepatic epithelial (L-02) cells are transferred into normal L-02 and THLE-3 cells, which are functionally active in the recipient cells. The results show that the exosomes from arsenite-transformed L-02 cells enhance miR-155 expression and the pro-inflammatory properties of normal L-02 and THLE-3 cells. Transformed cells transfer miR-155 into normal L-02 cells via exosomes. The inhibition of NF-κB by siRNA and inhibitor, which reduces miR-155 levels in exosomes derived from transformed L-02 cells, blocks inflammation. Arsenite-transformed cells secrete exosomes to enhance inflammation, but the inhibition of the synthesis of exosomes fails to stimulate inflammation. miR-155 is involved in exosome-mediated intercellular communication between neoplastic and normal liver cells. In addition, miR-155, IL-6, and IL-8 were over-expressed in the serum of arsenite exposure group. And there was a positive correlation between miR-155 and IL-6 or IL-8 levels. Further, exosomal miR-155 was up-regulated in the serum of arsenite exposure group. Thus, these results show that exosomes derived from transformed L-02 cells transfer miR-155 to surrounding cells, which induces pro-inflammatory activity of normal liver cells. The findings support the concept that exosomal miRNAs are involved in cell–cell communication during carcinogenesis induced by environmental chemicals. Highlights: NF-kB is involved in arsenite-induced increases of miR-155 levels in L-02 cells. miR-155 derived from arsenite-transformed L-02 cells is transferred to normal liver cells via exosomes. Exosomal miR-155 is involved in the pro-inflammatory properties of normal liver cells.